2014
DOI: 10.23885/1814-3326-2014-10-1-111-117
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the knowledge of Neuroptera and Raphidioptera of Mordovia (Russia)

Abstract: Резюме. Приводятся новые фаунистические данные о 19 видах сетчатокрылых и 3 видах верблюдок Мордовии. Семь видов сетчатокрылых и два вида верблюдок являются новыми для региона. Отмечен хорошо выраженный половой диморфизм у Chrysopa perla (Linnaeus, 1758): у всех 23 изученных самок тергиты брюшка сверху темные (черные или бурые, степень развития рисунка у разных особей очень варьирует), тогда как у всех 47 изученных самцов тергиты (кроме первого) лишены темной окраски; они зеленоватые, примерно одного цвета с з… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this Protected Area, there was a lack of systematic investigations of the invertebrate diversity before 2007. During 2007-2018, more than 5,000 invertebrate species have first been discovered for the Nature Reserve in the framework of an intensive investigation of the Protected Area's entomological diversity (Ruchin et al 2013, Makarkin & Ruchin 2014, Ruchin & Artaev 2016, Mandelshtam & Egorov 2017, Ruchin & Makarkin 2017, Ruchin & Mikhailenko 2018. Of these, 2,600 invertebrate species were firstly found for the whole Republic of Mordovia (Makarkin & Ruchin 2010, Bezina 2014, Bolshakov et al 2014, Budaeva & Ruchin 2014, Semenov 2016, Ruchin & Egorov 2017b, Bolshakov et al 2018, Chursina & Ruchin 2018a, including five species newly found for the Russian Federation (Mokrousov et al 2013, Tomaszewska et al 2018, Zemoglyadchuk et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…In this Protected Area, there was a lack of systematic investigations of the invertebrate diversity before 2007. During 2007-2018, more than 5,000 invertebrate species have first been discovered for the Nature Reserve in the framework of an intensive investigation of the Protected Area's entomological diversity (Ruchin et al 2013, Makarkin & Ruchin 2014, Ruchin & Artaev 2016, Mandelshtam & Egorov 2017, Ruchin & Makarkin 2017, Ruchin & Mikhailenko 2018. Of these, 2,600 invertebrate species were firstly found for the whole Republic of Mordovia (Makarkin & Ruchin 2010, Bezina 2014, Bolshakov et al 2014, Budaeva & Ruchin 2014, Semenov 2016, Ruchin & Egorov 2017b, Bolshakov et al 2018, Chursina & Ruchin 2018a, including five species newly found for the Russian Federation (Mokrousov et al 2013, Tomaszewska et al 2018, Zemoglyadchuk et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Old and recent collections of adult and larval stages of Myrmeleontidae from Volga-Ural plain, Lower Volga, Northern Caspian, and Eastern Caucasian territories have been collected, studied, and listed in special publications, mostly with participation of authors (Krivokhatsky 1993(Krivokhatsky , 2000(Krivokhatsky , 2012Krivokhatsky and Anikin 1996;Krivokhatsky and Zakharenko 1996;Krivokhatsky and Rokhletzova 2004;Rokhletzova and Krivokhatsky 2006;Rokhletzova 2000;Krivokhatsky et al 2003Krivokhatsky et al , 2016Ilyina and Krivokhatsky 2012;Ilyina et al 2014; Khabiev and Krivokhatsky 2014;Makarkin and Ruchin 2014). Previously published records based on doubtful identifications are listed and discussed (Krivokhatsky 2011).. New and interesting records are included in the annotated checklist.…”
Section: Methodsmentioning
confidence: 99%
“…West-Palaearctic boreo-nemoral species mainly confined to the dune landscapes at the seashores and large river banks. A safer known population exists at the river Borovka (Samara-Kinel' district) ( Figure 26 In addition to this population, the species was regularly recorded in the basins of the Don, Ural and Middle Volga (Krivokhatsky and Anikin 1996;Rokhletzova 2000;Rokhletzova and Krivokhatsky 2006;Makarkin and Ruchin 2014).…”
Section: Creoleon Plumbeus (Olivier 1811)mentioning
confidence: 96%